2021
DOI: 10.1155/2021/6658270
|View full text |Cite
|
Sign up to set email alerts
|

The Age-AST-D Dimer (AAD) Regression Model Predicts Severe COVID-19 Disease

Abstract: Aim. Coronavirus disease (COVID-19) ranges from mild clinical phenotypes to life-threatening conditions like severe acute respiratory syndrome (SARS). It has been suggested that early liver injury in these patients could be a risk factor for poor outcome. We aimed to identify early biochemical predictive factors related to severe disease development with intensive care requirements in patients with COVID-19. Methods. Data from COVID-19 patients were collected at admission time to our hospital. Differential bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…As the symptoms of COVID-19 vary widely, ranging from no symptoms to critical illness requiring urgent medical attention [ 45 , 46 ], an accurate prediction of disease progression is essential to guiding medical resource allocation to reduce mortality [ 47 ]. For instance, assigning patients with a relatively minor condition (e.g., mild pneumonia) to ambulatory care and those with a severe disease to the intensive care unit (ICU) [ 48 ]. In countries where medical resources are limited, a simple feasible indicator of disease severity may be critical for the effective allocation of medical supplies and manpower.…”
Section: Discussionmentioning
confidence: 99%
“…As the symptoms of COVID-19 vary widely, ranging from no symptoms to critical illness requiring urgent medical attention [ 45 , 46 ], an accurate prediction of disease progression is essential to guiding medical resource allocation to reduce mortality [ 47 ]. For instance, assigning patients with a relatively minor condition (e.g., mild pneumonia) to ambulatory care and those with a severe disease to the intensive care unit (ICU) [ 48 ]. In countries where medical resources are limited, a simple feasible indicator of disease severity may be critical for the effective allocation of medical supplies and manpower.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the clinical indicators discussed above, other features highlighted in Figure 6 were also found to have associations with COVID-19. Higuera-De-La-Tijera et al. (2021) showed the aspartate aminotransferase (AST) levels of severe COVID-19 patients were significantly higher than non-severe COVID-19 patients since AST is related to liver function.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major symptoms caused by COVID-19 is pneumonia, which is also a common infectious diseases threatening both human health and medical resources ( Zimlichman et al., 2013 ). Patients with mild pneumonia only need outpatient treatment, while severe patients have to be hospitalized or even admitted to the intensive care unit (ICU) for rescue ( Wei, 2020 ). Timely treatment for severe patients is significantly associated with reduced mortality ( Attaway et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies provided a comparison of patient groups combining severity and mortality (21,24). Many studies classified disease severity as patients who were admitted to an ICU or presented with at least one of the clinical manifestations listed in national guidelines for severe or critical diagnosis of COVID-19 (19,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Only three studies reported subjects with similar ages between groups (p > 0.05) (30,37,38), and seven studies reported significantly different male:female ratios (p < 0.05) (18,22,37,(39)(40)(41)(42).…”
Section: Study Characteristicsmentioning
confidence: 99%